Entrepreneurial Education as a Panacea for National Integration and Security Sustainability in Nigeria: A Literature Review - Abdullahi Dauda; Garga Esther (Eurasian Journal of Management & Social Sciences, 2023)
Entrepreneurship education can be used to advance awareness, educate and unite a nation, destroy ignorance and develop a strong economy that will enable the achievement of sustainable security. The paper’s goal is to evaluate entrepreneurship education as a solution for Nigerian national integration and security stability. The methodology used for collection of data is content analysis/secondary source from publications like journals, magazines, newspapers and similar sources. Quantitative method was also used in conducting this study. The reviewed papers related to this study’s findings found significant relationship between entrepreneurial education, National integration and security sustainability. Conclusion: entrepreneurship serves as a vital tool for bringing the country together by fostering the growth of the young and decent citizens of the country. To prepare the youth for independence, it is advised that the government permit entrepreneurship education to be taught at all levels of our educational system, to equip the youth for self-reliance and reduce crime in society.